Safranin-O-Mediated Photodynamic Inactivation of Microorganisms Reduces Milk Contaminating Bacteria Count and Prevented New Cases of Mastitis - Rodrigues, B. M.; Saraiva, B. B.; da Silva Junior, R. C.; Campanholi, K. S. S.; Alcalde, C. R.; Pozza, P. C.; Madrona, G. S.; Pozza, M. S. S. (Tropical Animal Science Journal, 2023)
The objectives of this study were to evaluate the antimicrobial capacity of the photosensitizer (PS) safranin-O (Sf), through antimicrobial photodynamic therapy (PDTa), against strains of Pseudomonas fluorescens (PV1, PVh, and PC3) and Staphylococcus aureus (SV1, SV3, SV5, SC5, SC6, and SC8) isolated from milk from cows and goats and the biofilm formation on equipment. To evaluate the effectiveness of the formulation, studies were carried out through in situ applications of the Sf hydrogel as post-dipping in lactating cows and goats. Antibiogram tests showed the resistance of Staphylococcus aureus isolates to ampicillin, trimethoprim, and tetracycline. In the in vitro assays in bovine milk, the PDTa reduced the P. fluorescens (PV1) counts by 17.4% (p